DEVELOPMENT OF AISS APP (LOCAL CULTURE OF INDONESIA STOCK SIMULATOR APPLICATION) AS STOCK INVESTMENT LEARNING MEDIA - Selvi Sehiling; Ahmad Ajib Ridlwan (JPIM (Jurnal Penelitian Ilmu Manajemen), 2023)
The purpose of this study is to develop stock investment learning media that is integrated with android-based cultural insights. This research belongs to the research and development. The research and development used in this study is represented by the Borg & Gall version model which has 10 stages; however, empirically it can be summerized into 4 stages, namely introduction, development, validation and implementation. The subjects in this study are divided into two groups: expert lecturers as validators of applications and materials and users between the ages of 15-20. The object of the study is the interest in stock investment. This study’s writing method is a descriptive method with a quantitative-qualitative approach. Based on an online survey conducted by the researchers, it shows that out of 90 respondents, 74 percent of them had no idea about the stock issuance system and 35.6 percent of respondents were interested to stock investment, and 51.1 percent had a desire to invest in stocks but did not know how to do so. The validity results of AISS APP development products based on expert validator assessments are declared valid, having a good category and able to be applied as learning media. As for the basis of limited trials, the result is valid, very good and able to be applied